Seasonal feeding habits and ontogenetic diet shift of black bullhead (Ameiurus melas) in Lake Sava (Serbia) - Jaćimović, Milica; Krpo-Ćetković, Jasmina; Skorić, Srefan; Smederevac-Lalić, Marija; Hegediš, Aleksandar (Archives of Biological Sciences, 2021)
Paper description: The black bullhead is one of the most successful non-native fish species in European freshwaters. Feeding habits of individuals caught in Lake Sava were analyzed by applying the following indices: vacuity index, frequency of occurrence, numerical abundance, and prominence value; trophic niche breadth and seasonal trophic diversity were calculated using the Shannon index. The diet spectrum was comprised of 16 prey categories from five groups: Mollusca, Crustacea, Insecta, Teleostei and plants. This species is a generalist and opportunist that enters into competitive and predatory relationships with native fish species. Abstract: The black bullhead is an invasive species that forms dense populations and has a negative impact on the native ichthyofauna. Recent studies indicate that it is one of the most dominant invasive fish species in Serbian waters. Feeding habits based on stomach contents of individuals caught in Lake Sava were analyzed as a first step towards evaluating its possible negative impact on the native fish fauna of the lake. The following indices for diet analysis were applied: vacuity index, frequency of occurrence, numerical abundance and prominence value. Trophic niche breadth and seasonal trophic diversity were calculated using the Shannon’s index. The diet spectrum comprised 16 different prey categories from five groups: Mollusca, Crustacea, Insecta, Teleostei and plants. Fish were the main prey in all seasons, followed by aquatic invertebrates. Plant material and terrestrial insects were used as food in relatively small quantities. Predation on fish eggs was also detected. Our research confirmed that this species is an opportunistic generalist. An ontogenetic diet shift was also detected. The lowest value of trophic diversity was found in age 1+ individuals (H=1.39), while the highest was found in age 3+ individuals (H=2.00). The widest niche breadth was recorded in spring 2011 (H=2.12).